Analysis of code mixing on lifni sanders beauty campaign in the female daily network video youtube channel - Aynun Niza; Dwi Setyadi; Yuli Kuswardani (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
The development of technology nowadays makes most of people have Youtube account including beauty vloggers. They often share the information about make-up products that they use in their captions. Sometimes, they mix some languages in their captions, for example from Indonesian to English. Therefore, the focus of this research is to analyze the use of Indonesian-English code mixing done by Lifni Sanders. In this research, the researcher tried to answer 2 research questions. First, the researcher found out the types of code mixing found in the data of the research. Second, the researcher analyzed the context of code mixing which appear on Lifni Sanders Beauty Campaign in The Female DailyNetwork Video YouTube Channel.In order to answer the first research questions, the researcher applied the theories proposed by Hoffman (1991). In the second questions, the researcher applied the theories proposed by Holmes (1992).Furthermore, in this research the main sources of the data were Lifni Sanders Beauty Campaign in the FemaleDailyNetwork Video Youtube Channel.The researcher applied purposive sampling strategy in order to collect the data. Based on the analysis, there were 183 cases of code mixing. The researcher concluded that there were 149 cases of intra-sentential code mixing and 15 cases of intra-lexical by the addition of Indonesian affixes -nya, di-, andse-. Besides, there were 19 cases of involvement in a change of pronunciation. The researcher found that there were 8 data included in the participant of interaction, 3 data included in the setting of interaction, 11 data on the topic of interaction, and finally 3 data included in the purpose of interaction.